2022
DOI: 10.3389/fnagi.2022.936862
|View full text |Cite
|
Sign up to set email alerts
|

The stress hyperglycemia ratio is associated with the development of cerebral edema and poor functional outcome in patients with acute cerebral infarction

Abstract: Background and purposeAbsolute hyperglycemia at admission has been shown to be associated with the development of cerebral edema (CED) after acute cerebral infarction. Stress hyperglycemia is a more objective reflection of hyperglycemic state than absolute hyperglycemia. However, studies on the associations between stress hyperglycemia and CED are limited. We aimed to explore the associations of stress hyperglycemia, measured by stress hyperglycemia ratio (SHR), with the development of CED and poor functional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 40 publications
(64 reference statements)
1
11
0
Order By: Relevance
“…Consequently, SHR1 and SHR3 which were calculated from FPG represented stronger association and higher predictive values to the fatal outcomes than SHR2 and SHR4. Increasing hyperglycemia in AIS patients escalates oxidative stress, neurohormonal derangement, and inflammatory cytokines, thereby perpetuating a vicious cycle that exacerbates hyperglycemia [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, SHR1 and SHR3 which were calculated from FPG represented stronger association and higher predictive values to the fatal outcomes than SHR2 and SHR4. Increasing hyperglycemia in AIS patients escalates oxidative stress, neurohormonal derangement, and inflammatory cytokines, thereby perpetuating a vicious cycle that exacerbates hyperglycemia [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…A final decision was made by a senior neurologist (M.L) if two researchers could not reach a consensus. Presence of mild degree of hemorrhagic transformation was permitted, since it was not considered to result in mass effect [21]. Secondary outcomes were one-month death and three-month poor functional outcome (modified Rankin scale (mRS) ≥ 3).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 13 patients were excluded: 3 patients developed bilateral ischemia; 1 patient was diagnosed with recurrent stroke at this visit; 6 patients developed parenchymal hemorrhage type 2 before imaging evaluation for MBE; 3 patients were with absence of blood pressure and heart rate measurements (Figure S1). We finally enrolled 162 LHI patients (43.8% males, mean age 70.3 years old) with a median NIHSS of [16][17][18][19][20][21]. The median delay from onset of symptoms to admission was 5 h (IQR 3-12).…”
Section: Baseline Characteristics Of Patientsmentioning
confidence: 99%
“…Regarding cerebrovascular diseases, research suggests a significant positive correlation between higher SHR quartiles and an increased risk of ischemic stroke transformation to hemorrhage in patients [11]. Additionally, the SHR is independently associated with the severity of post-acute ischemic stroke brain edema, unfavorable functional outcomes, and post-acute ischemic stroke mortality [12]. In cardiovascular diseases, the results of a multicenter prospective study in China demonstrated a correlation between high SHR and increased long-term mortality [13].…”
Section: Relation To Previous Researchmentioning
confidence: 99%